Association of muscle strength with cardiovascular risk in Korean adults: Findings from the Korea National Health and Nutrition Examination Survey (KNHANES) VI to VII (2014–2016) - Lee, Mee-Ri; Jung, Sung Min; Kim, Hwa Sung; Kim, Yong Bae (Medicine (Baltimore), 2018)
There are few existing studies that examine the association between muscle strength and cardiovascular disease (CVD) risk stratified by sex. Evaluation of the handgrip strength is a simple, quick, and inexpensive method to measure muscle strength. This study assessed the association of handgrip strength with the risk of CVD in the Korean general population.Data were derived from a subset of an ongoing nationally representative survey: the Korea National Health and Nutrition Examination Survey (KNHANES), 2014 to 2016, which included 8576 participants aged 40 to 79 years (men: 3807; women: 4769). Individual CVD risk was evaluated by calculating the atherosclerotic cardiovascular disease (ASCVD) risk score and the Framingham risk score (FRS) in subjects aged 40 to 79 years without prior CVD.Multivariate linear regression analysis revealed a significant inverse association (in both men and women) between relative handgrip strength and cardiovascular risk factors, including blood pressure, levels of fasting glucose and triglycerides, waist circumstance, FRS, high sensitivity C-reactive protein levels, and ASCVD risk. A significant positive association between relative handgrip and a low level of high density cholesterol levels in both men and women was identified. In both men and women, subjects in the lowest quartile of handgrip strength had an increased risk of CVD compared with those within the highest quartile (odds ratio range 2.05-3.03).The results of this study suggest that increased handgrip is associated with a lower degree of cardiovascular risk in both men and women. Longitudinal studies are needed to examine the association between muscle strength and cardiovascular risk.